Invasive aspergillosis in patients admitted to the intensive care unit with severe influenza: a retrospective cohort study - Schauwvlieghe, Alexander F A D; Rijnders, Bart J A; Philips, Nele; Verwijs, Rosanne; Vanderbeke, Lore; Van Tienen, Carla; Lagrou, Katrien; Verweij, Paul E; Van de Veerdonk, Frank L; Gommers, Diederik; Spronk, Peter; Bergmans, Dennis C J J; et al. (The lancet respiratory medicine, 2018)
Invasive pulmonary aspergillosis typically occurs in an immunocompromised host. For almost a century, influenza has been known to set up for bacterial superinfections, but recently patients with severe influenza were also reported to develop invasive pulmonary aspergillosis. We aimed to measure the incidence of invasive pulmonary aspergillosis over several seasons in patients with influenza pneumonia in the intensive care unit (ICU) and to assess whether influenza was an independent risk factor for invasive pulmonary aspergillosis. We did a retrospective multicentre cohort study. Data were collected from adult patients with severe influenza admitted to seven ICUs across Belgium and The Netherlands during seven influenza seasons. Patients were older than 18 years, were admitted to the ICU for more than 24 h with acute respiratory failure, had pulmonary infiltrates on imaging, and a confirmed influenza infection based on a positive airway PCR test (influenza cohort). We used logistic regression analyses to determine if influenza was independently associated with invasive pulmonary aspergillosis in non-immunocompromised (ie, no European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group [EORTC/MSG] host factor) influenza-positive patients (influenza case group) compared with non-immunocompromised patients with severe community-acquired pneumonia who had a negative airway influenza PCR test (control group). Data were collected from patients admitted to the ICU between Jan 1, 2009, and June 30, 2016. Invasive pulmonary aspergillosis was diagnosed in 83 (19%) of 432 patients admitted with influenza (influenza cohort), a median of 3 days after admission to the ICU. The incidence was similar for influenza A and B. For patients with influenza who were immunocompromised, incidence of invasive pulmonary aspergillosis was as high as 32% (38 of 117 patients), whereas in the non-immunocompromised influenza case group, incidence was 14% (45 of 315 patients). Conversely, only 16 (5%) of 315 patients in the control group developed invasive pulmonary aspergillosis. The 90-day mortality was 51% in patients in the influenza cohort with invasive pulmonary aspergillosis and 28% in the influenza cohort without invasive pulmonary aspergillosis (p=0·0001). In this study, influenza was found to be independently associated with invasive pulmonary aspergillosis (adjusted odds ratio 5·19; 95% CI 2·63-10·26; p<0·0001), along with a higher APACHE II score, male sex, and use of corticosteroids. Influenza was identified as an independent risk factor for invasive pulmonary aspergillosis and is associated with high mortality. Future studies should assess whether a faster diagnosis or antifungal prophylaxis could improve the outcome of influenza-associated aspergillosis. None.